Kaunas Dominicans – Chaplains of Kaunas Benedictine Nuns in the 17th–19th Centuries - Kamuntavičienė, Vaida (History / Istorija, 2025)
The article analyses who were the chaplains of the Kaunas Benedictine nunnery, founded in 1624, and reveals the role of the Bishop of Vilnius in appointing chaplains and confessors. The research allowed to find out the clergy who participated in the ceremony of the perpetual vows of Kaunas Benedictines. The study showed that the most frequent persons to serve as confessors of the Kaunas Benedictines were the parson of the parish church in Kaunas, the priest of the Church of the Holy Cross in Kaunas, or the Kaunas Dominicans. Some Jesuits, Bernardines, Augustinians, and Discalced Carmelite monks were also occasionally Benedictine confessors. The article shows the relations between various Kaunas clergy.